Sensory Gardens - Eva C. Worden; Kimberly A. Moore (EDIS)
All gardens can stimulate the senses. Some gardens stimulate the senses to a greater degree than others. In sensory gardens, plants and other design elements are selected with intention to provide experiences for seeing, smelling, hearing, touching, and tasting. Some sensory gardens are devoted specifically to one sense, such as a fragrance garden. Others may focus on several senses, with separate sections devoted to each sense. A third approach is a blend that enlivens all of the senses throughout the garden.  This document is ENH981, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date March 24, 2003. Reviewed June 2004.